The predictive value of sequential cervical length screening in singleton pregnancies after cerclage: a retrospective cohort study. Issue 1 (December 2016) - Pils, Sophie; Eppel, Wolfgang; Promberger, Regina; Winter, Max-Paul; Seemann, Rudolf; Ott, Johannes
Abstract Background There are few valid predictors for preterm delivery after cerclage. Experience with a screening program that included four sequential cervical length measurements in singleton pregnancies after cerclage is reviewed. Methods In this retrospective cohort study, 88 singleton pregnancies after cerclage were included. Cervical length (CL) measurements were performed perioperatively and at weeks 16 + 0, 18 + 0, 20 + 0, and 22 + 0 by transvaginal ultrasound. Predictive factors for early preterm delivery included patient characteristics, obstetric history and CL measurements and were analyzed separately for women with ultrasound-indicated cerclage and those with history-indicated cerclage. Women with emergency cerclage were excluded. Results In women with delivery <35 weeks, CL declined from the 16 + 0 to the 22 + 0 weeks of gestation (p  = 0.009). In univariate analysis, all CL measurements were predictive for delivery <35 weeks in women who underwent ultrasound-indicated cerclage and in women who received a history-indicated cerclage, whereas in multivariate analysis only CL three to six days after cerclage remained significant (odds ratio 0.85, 95 % CI 0.73–0.98). In women with ultrasound-indicated cerclage, optimized cut-off was ≤20 mm (specificity 83.8 %, sensitivity 84.2 %). Conclusions CL measured three to six days after cerclage placement provides the best information about the risk for delivery <35 weeks.